Pendampingan Pembuatan Cocopeat dari Sabut Kelapa Dalam Peningkatan Ekonomi Masyarakat - Eka Chyntia; Siti Maisyarah; Ana Zahara; Shalawati Shalawati; Maisyuri Maisyuri; Hikalmi Hikalmi (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2025)
AAF Hamlet, located in Paloh Lada Village, Dewantara Subdistrict, North Aceh, has an abundant supply of coconut husk waste. However, this waste has not been utilized optimally, leading to environmental pollution and the neglect of local economic potential. Through this community service initiative, the implementing team aimed to empower local residents by introducing and training them in the processing of coconut husk waste into cocopeat—a valuable and eco-friendly growing medium. The program was carried out in three main stages: an initial awareness session to provide basic understanding, technical training on processing coconut husks into cocopeat, and production mentoring to ensure the sustainability of acquired skills. The results showed a significant increase in participants’ knowledge and skills regarding coconut husk waste management. Moreover, the initiative sparked community interest in developing cocopeat as a new entrepreneurial opportunity The short-term impact included immediately applicable new skills, while the long-term impact involved the emergence of business opportunities that support household income and environmental conservation. These outcomes highlight the importance of waste processing based on local potential as an effective strategy for community empowerment and sustainable economic development.